Analisis Integrasi Islam dan Budaya Minangkabau dalam Tradisi Batagak Penghulu Berdasarkan Perspektif Al-Qur’an - Althafullayya, Muhammad Raffin; Akbar, Ali (Jurnal Pendidikan Islam, 2024)
The Batagak Penghulu tradition in Minangkabau can be considered as a form of integration between traditional and Islamic values, where Islamic principles are the basis for implementing this tradition. In this tradition, religious values and Islamic teachings are reflected in various aspects, such as the election of leaders, the deliberation process, and cooperation in order to achieve goodness and justice. The process of selecting the headman involves the participation of all components of society, demonstrating the principle of deliberation recommended in Islam. The chosen leader must meet leadership criteria in accordance with Islamic teachings, such as being honest, trustworthy, wise, and able to convey teachings well. The Qur'an also emphasizes the importance of just leadership and dual responsibility towards Allah SWT and society. The concept of deliberation, explained in the Qur'an, provides the basis for decision making in the traditional Batagak Penghulu process. This deliberation process not only reflects traditional values, but is also in line with Islamic principles which encourage justice, togetherness and problem solving through consensus. Through qualitative research methods and content analysis, this research provides an in-depth understanding of the integration between custom and Islam in the Batagak Penghulu tradition. The Batagak Penghulu tradition in Minangkabau reflects the harmonization between traditional values and Islamic teachings. The process of appointing the headman, deliberation, leadership and cooperation in this tradition shows harmony with the Islamic principles contained in the Al-Qur'an. This tradition is not only a unique cultural heritage, but also a manifestation of community life that is firmly rooted in Islamic religious values.